Muhaawalatu Al-Muhaadhir Ila Tarqiyyati Al-Ansyitoti Al-Ta'limiyati Fi Ta'lim AL-Lughah Al-'Arabiyah Khilala Waba' Covid-19 - Nuryani Nuryani; Muhamad Fatoni; Rina Dian Rahmawati; Muhammad Nur Kholis; Moh Sholeh Afyuddin (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2023)
This study aims to analyze: (1) the lecturer's attempts to upgrade teaching activities in Arabic language teaching during the Covid-19 pandemic for students of the Department of Teaching Arabic; (2) the factors hindering the lecturer in promoting teaching activities in teaching Arabic during the Covid-19 pandemi; and (3) the factors that help the lecturer in promoting teaching activities in teaching Arabic during the Covid-19 epidemic. Type of this research is a case study with a qualitative approach. The method of data collection is: interviewing, observing, documenting and analyzing the results in three steps: data collection, simplifying or reducing data, data presentation, and conclusion. The results show that: 1) efforts by lecturers to promote Arabic teaching and learning activities during the Covid-19 pandemic, including preparing educational plans according to needs; realization of educational planning; Carrying out appropriate evaluations. 2) factors that facilitate the online learning process during the COVID-19 pandemic include learning flexibility, a supportive internet connection; the government policies and institutions support; availability of supporting facilities; lecturers who are quite proficient in using technology, and intensive attention from lecturers; 3) Some of the obstacles faced by lecturers during distance learning, namely: the difficulty of having two-way communication between lecturers and students; internet connection is not evenly distributed in several places, students cannot take part in intensive learning; the lecturer's explanation is less interesting; lack of student participation in learning; sudden adaptation difficulties for some lecturers.